Evaluation of Some Sums of Polynomials in Fq[t] - Adama Diene (Journal of Applied Mathematics, 2019)
We prove the polynomial analogues of some Liouville identities from elementary number theory. Consequently several sums defined over the finite fields Fq[t] are evaluated by combining the results obtained and some of the results from sums of reciprocals of polynomials over Fq[t].